Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Simplify the following:

i) [tex]\(\sqrt{45} - 3\sqrt{20} + 4\sqrt{5}\)[/tex]

Solution:
[tex]\[
\begin{aligned}
& \sqrt{45} - 3\sqrt{20} + 4\sqrt{5} \\
&= \sqrt{3 \times 3 \times 5} - 3\sqrt{2 \times 2 \times 5} + 4\sqrt{5} \\
&= 3\sqrt{5} - 6\sqrt{5} + 4\sqrt{5} \\
&= \sqrt{5}
\end{aligned}
\][/tex]

ii) [tex]\(\frac{2+\sqrt{3}}{2-\sqrt{3}}\)[/tex]


Sagot :

Certainly! Let's tackle part (i) of your question in detail:

To simplify the expression: [tex]\(\sqrt{45}-3 \sqrt{20}+4 \sqrt{5}\)[/tex]

Step-by-step solution:

1. Simplify each square root term individually:

- [tex]\(\sqrt{45}\)[/tex]:
[tex]\[ \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \times \sqrt{5} = 3\sqrt{5} \][/tex]

- [tex]\(-3 \sqrt{20}\)[/tex]:
[tex]\[ -3 \sqrt{20} = -3 \times \sqrt{4 \times 5} = -3 \times \sqrt{4} \times \sqrt{5} = -3 \times 2 \sqrt{5} = -6 \sqrt{5} \][/tex]

- [tex]\(4 \sqrt{5}\)[/tex] is already in its simplest form.

2. Substitute the simplified terms back into the original expression:
[tex]\[ \sqrt{45} - 3 \sqrt{20} + 4 \sqrt{5} = 3 \sqrt{5} - 6 \sqrt{5} + 4 \sqrt{5} \][/tex]

3. Combine like terms (terms involving [tex]\(\sqrt{5}\)[/tex]):
[tex]\[ 3 \sqrt{5} - 6 \sqrt{5} + 4 \sqrt{5} = (3 - 6 + 4) \sqrt{5} = 1 \sqrt{5} = \sqrt{5} \][/tex]

So, the simplified form of the expression is:
[tex]\[ \sqrt{5} \][/tex]

Final Answer:
[tex]\[ \sqrt{45} - 3 \sqrt{20} + 4 \sqrt{5} = \sqrt{5} \][/tex]

Feel free to reach out if you have any questions on part (ii) or any other queries!